Produccion y demanda de habichuela en los paises en desarrollo: Dtos preliminares - Janssen, W. (International Center for Tropical Agriculture, 1987)
The most important aspects of snap bean consumption, marketing, processing, and production are emphasized; topics for future research and development are highlighted. The role of snap beans in comparison with other vegetables is discussed. Vegetable demand grows as a consequence of the urbanizing process and income increase. The role of snap beans among vegetables depends on their price, quality, and availability. Price and availability are mostly determined by the marketing system as shown by high margins (100- 150 percent the price of the grower). Quality depends on the grower to a great extent; thus, genetic efforts to improve the quality of the product have more impact than work on increasing yield and reducing production costs. The area planted to snap beans is less than 3 percent that of beans; however, the value of snap bean production to the consumer is 27 percent that of beans. Snap beans are considerably important in China, Taiwan, and some Latin American countries. For snap bean development to be stimulated, it is necessary to establish a seed distribution and production network, to decrease commercialization costs, and to introduce the producer in the urban marketing system. (CIAT)